A biochemical and immunological study of ovine adrenal mitochondrial electron transport proteins involved in steroidogenesis - De Kock, Ilze (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.